Surface reactivation of FeNiPC metallic glass: A strategy for highly enhanced catalytic behavior. (September 2019) - Liang, Shun-Xing; Zhang, Wenchang; Wang, Weimin; Jia, Guohua; Yang, Weiming; Zhang, Lai-Chang
Abstract: With intrinsically disordered atomic structure, metallic glasses (MGs) have been extensively studied as advanced catalysts. Although the nature of widely tunable atomic composition in MGs facilitates accommodation in different catalytic environments, it may also induce the decline of catalytic activity due to surface effect. The role of surface of MGs is still not fully understood. In this work, an Fe50 Ni30 P13 C7 (FeNiPC) glassy ribbon was found to have a strong-binding surface layer with the superior anticorrosion but low catalytic ability. Nevertheless, an effective elimination of surface layer by chemical dealloying could highly promote the catalytic ability of FeNiPC glassy ribbons from 20 min to only 10 min for brilliant black BN dye degradation. Further investigation revealed that chemical dealloying could effectively dissolve the surface layer of FeNiPC glassy ribbons induced reactivation of surface that was previously buried under the strong oxide layer, instead of generating nano-porous structured surface. The reactivation of ribbon surface effectively optimized active reaction sites and the re-exposure of Fe, Ni and P with zero-valent state formed galvanic cells by atomic clusters leading to the acceleration of catalysis. The insight and revelation of intrinsic surface activity in this work provide an effective way to highly promote the catalytic ability of MGs. Graphical abstract: Image 1 Highlights: Strong surface stability in FeNiPC ribbons has been revealed. Dye degradation rate of dealloyed FeNiPC ribbons is 2 times higher than that of the as-received counterparts. Brilliant black BN is fully degraded in only 10 min by dealloyed FeNiPC ribbons. A mechanism of surface reactivation of dealloyed FeNiPC ribbons is revealed. Optimized active sites and re-exposure of Fe 0, Ni 0 and P 0 are found in dealloyed ribbons.